PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA PT. INDOMARCO ADI PRIMA DI DAMPYAK TEGAL - Medi Tri Purwanto (Jurnal Strategik, 2016)
ABSTRAK This study examines the effect of product quality and price on purchasing decisions at PT. Indomarco Adi Prima. Respondents in this study were samples who were shopping at PT. Indomarco Adi Prima. The number of respondents who made the sample of this study were 50 people. In determining the sample used in this study was purposive random sampling, while to find out the relationship between variables the researcher used a data quality analysis calculation method consisting of (1) Validity Test and (2) Reliability. Then to find out the influence between the variables the researcher used classical assumption analysis consisting of (1) Normality test (2) Multicollinearity Test (3) Heteroscedasticity Test (4) T test and (6) F test with analysis tool using SPSS version 20 for windows The results of this study show that the quality variables of the porduk have a significant effect and the price variable has a significant effect and from the simultaneous test results it influences the purchasing decisions at PT. Indomarco Adi Prima. Keywords: Product quality, price and purchase decision